Book Review - Through Turbulent Terrain: Trade of the Straits Port of Penang - Ku, Boon Dar (Universiti Kebangsaan Malaysia, 2019)
The monograph, Through Turbulent Terrain: Trade of the Straits Port of Penang tells the tumultuous history of Penang’s economy which had suffered through many trials in its attempt to remain competitive and relevant against the test of time. This is thanks to the unique history of how the island developed, from 1786. Dr Loh Wei Leng and Jeffrey Seow traced Penang’s trade history with ports in the East and the West. The establishment of Penang Island was due to the fact that it was located right in between India and Canton, making it a most suitable port of call. The island went on to become British East India Company’s port for collection and distribution of goods in the Straits of Malacca.